Tasks, Employment and Wages: An Analysis of the German Labor Market from 1979 to 2012 - Anna Katharina Pikos; Stephan L. Thomsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The literature has found evidence for a wage polarization depending on routine and non-routine working tasks. Using unique German survey data we ask whether wage polarization coincides with polarization in job satisfaction. First, we find that contrary to what polarization predicts, routine cognitive tasks are associated with higher wage. Second, satisfaction across tasks has converged rather than diverged. The main driver for these two findings are routine cognitive tasks which do not lower satisfaction but instead more often than not increase it. Evidence for polarization arises from the facts that non-routine analytic tasks tend to increase and routine manual to decrease satisfaction. But due to a persistent positive effect of routine cognitive tasks, we do not find clearcut satisfaction polarization.
Keywords: J24; J28; J00; 330